Why Men and Women Want to Leave? Turnover Intent Among Public Procurement Officers. Issue 7 (October 2018) - Ali, Susannah Bruns; Bishu, Sebawit; Alkadry, Mohamad
This study examines differences in turnover intent between men and women with the aim of building a better understanding of factors that contribute to disparities between the sexes and creating more useful recruitment and retention strategies. The study proposes a theoretical framework where personal, human capital, organizational, and structural/community factors contribute to the desire to change jobs. The focus here is on procurement officers as their role is critical in public sector organizations from the local to the federal level. They also are unique in that their skill set is transferable from one organization to another and procurement officers have relatively high opportunities to move both within and between organizations. The study finds that there are important differences in the drivers of turnover intent between men and women and that most differences lie in the personal, human capital, and organizational categories.